Penerapan Metode MOOSRA Dalam Rekomendasi Pemilihan Calon Panitia Pemungutan Suara (PPS) - Elfrianti Fransiska Hutahaean; Oktavia Wulandari; Nelly Astuti Hasibuan (TIN: Terapan Informatika Nusantara, 2022)
Voting Committee is a committee formed by Regency/Municipal KPU/KIP to carry out General Elections (elections) in other villages or sub-districts. The committee is a group of people appointed or elected to consider or take care of matters assigned to the group. General elections in a village become an activity that must be carried out every year that has been determined, where the community will vote to choose who deserves to be a leader through ballots (Balot). In the general election (Pemilu) a committee is needed to carry out the voting called (PPS). This Voting Committee (PPS) will help the community to carry out the general election process later at every level in accordance with the rules made. To choose the committee an Alternative and certain criteria. In this case the Siregar village head has the opportunity to recommend candidates who will become the voting committee who will serve in the village, but the lack of understanding of knowledge about what criteria must be owned by the voting committee makes it often wrong to recommend PPS candidates, and still manually process data from candidates to be recommended so that it takes a long time. Therefore a system is needed using certain methods to solve these problems, in this case the author uses a Decision Support System with the Multiobjective Optimization method on the Basis of Ratio Analysis (MOOSRA) because it can determine criteria that meet the requirements and deserves to be recommended this method is also considered capable of solving the problem because with this system an appropriate and accurate decision can be taken/drawn. Suara (PPS), which is the first alternative with the name Rohani Butar-Butar, is the best alternative with a total value of 4,812